Penambahan Fitur Green Cool-Hot Box Pada Skuter Listrik Tipe Super E-Bike Model Es-009 Berbasis Termoelektrik - Mohamad A Muhidin; Awaludin Martin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The addition of green cool-hot box on the electric scooter that has a cooling feature, require a refrigeration unit that is able to be applied on the electric scooter. Peltier elements selected for use as a cooler in the cool green because of the small box that can be operated on electric scooter box has limited space and can also be operated at a voltage of 12 volts . The design is done in this case is to modify the existing back box on an electric scooter. Peltier element used is type TEC1 12706. The ability of cold side Peltier element is utilized for cooling process in electric scooter box .Lowest temperature green cool box with dissipates heat from the hot side to environment without load of water is 13,8oC . and with a maximum load of 960 ml of water was 20,6oC . Utilization of waste heat from the hot side of the heat sink for space heating will affect the cooling process in the refrigerator. The temperature of the cooling chamber will be increase when compared to the temperatur of the hot side heatsink discharged into the Environment.Kata Kunci : Element Peltier, Termoelectric, Cool-hot box, COP